EFFECT OF BLACK GRAPE EXTRACT ON CD4+ and CD8+ EXPRESSION IN MICE INFECTED WITH Salmonella typhimurium - rian anggia destiawan; septyana eka rahmawati; anas fadli wijaya; Ahdiah Imroatul Muflihah; Mutia Hariani Nurjanah; Sholihatil hidayati; Ni Ketut Yuliana sari (Jurnal Biosains Pascasarjana, 2022)
Salmonelosis is a disease caused by the Salmonella sp. that causes a decrease in CD4+ expression. Black grape can boost the immune system through CD4+/CD8+ proliferation. The purpose of this study was to evaluate the activity of black grape extract to CD4+ and CD8+ expression in mice infected with Salmonella typhimurium. Research method is extract of black grapes, Salmonella typhimurium 108 infection, bacterial evaluation, extract therapy, flowcytometery examination, and 95% Anova test. The results of Anova test showed that the expression of CD4+ and CD8+ is not different. Biologically, an increase in CD4+ and CD8+ expression at doses of 100 mg/KgBB. A decrease in CD4+ and CD8+ expression at doses of 200 mg/KgBB and 400 mg/KgBB. Conclusion, biologically, black grape extract can increase the expression of CD4+ and CD8+ at low doses, as well as may decrease the expression of CD4+ and CD8+ at moderate to high doses.